(3JSgjd GdahGFO hJcejd GdebGUOs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3CMeO Hf Ydi Gdchai s)
(3ChdgG (B:s
(3bGd GdTjN Hf eGdc MGeOkG ddg QH GdYGdejf heUdjkG Ydi fHjg eMeO SjO GdeQSdjf hYdi Bdg hUMGHJg CLeYjf gPG cJGH ai GdfMh LYdJg HYhf Gddg eSJhajkG dCUhdg s
(3BNQgG (B:s
(3hgPG eeG jfbGO Edjg hdG jbGS Ydjg s
(3HBNQgG UhQI SeGY efbhdI ef GdCUds
(3Ydi GdEeGe CHj MjGfs
(3hbO JVef gPG GdSeGY ahGFO cKjQI Yf GdTjN CHj MjGfs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs